2007
DOI: 10.1021/jp0746143
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Structure of Small 4He Clusters Seeded with HF, HCl, and HBr Molecules

Abstract: Diffusion Monte Carlo calculations are performed for ground and excited rotational states of HX(4He)N, complexes with N Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 84 publications
2
21
0
Order By: Relevance
“…They concluded that it is the strength and anisotropy of the He-molecule interaction, rather than the gas phase rotational constant itself, that is mainly responsible for the reduction of the rotational constant in the nanodroplet regime. A more recent study 7 of HX-He complexes with X = F, Cl, and Br obtained results in agreement with the conclusions of ref. 16.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…They concluded that it is the strength and anisotropy of the He-molecule interaction, rather than the gas phase rotational constant itself, that is mainly responsible for the reduction of the rotational constant in the nanodroplet regime. A more recent study 7 of HX-He complexes with X = F, Cl, and Br obtained results in agreement with the conclusions of ref. 16.…”
Section: Introductionsupporting
confidence: 90%
“…All calculations described in this paper assume pairwise molecule-He interaction potentials. The PESs for the HF-He, HCl-He and HBr-He dimers have been described elsewhere 7 and consist of the following expansion in Legendre polynomials…”
Section: Potential Energy Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…We first compared our predicted geometries and interaction energies with the accurate values available from the literature for the majority of the presently investigated He(M) systems (the only previously unreported are the HeClR, R = CN, CCH, OH, SH, CH 3 , SiH 3 ). With respect to these benchmark data (listed in Table S3), typically obtained at the CCDS(T) or SAPT levels of theory with very large basis sets, the bond distances quoted in Figure , and the EintSAPT listed in Table feature a mean unsigned deviation (MUD), respectively, of 0.0908 a 0 , and 1.20 cm −1 .…”
Section: Resultsmentioning
confidence: 99%